Domestic Wastewater Disinfection Planning for Constructed Wetland Treatment Effluent - Giovanni Ruly Putra; Betanti Ridhosari; Evi Siti Sofiyah; Nurulbaiti Listyendah Zahra; Ariyanti Sarwono; I Wayan Koko Suryawan (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
Excessive water consumption to meet water needs has changed aquatic water quality and quantity. Focus on domestic wastewater treatment via built wetlands. Disinfection protects humans against disease-causing viruses, bacteria, and protozoan parasites in wastewater. This study planned the disinfection of artificial wetland wastewater to fulfill microbiological criteria. From the examined data, each unit's design criteria and disinfection effectiveness for the created wetland outlet in the WWTP unit will be discussed. The created wetland must process 8696 cfu/100mL of fecal coliform. Despite good processing efficiency, 94% of fecal coliforms do not fulfill quality criteria. WWTP's wetland emits 8.011 mg/L of Ammonia. 90% chlorine costs Rp. 35,000/kg on the market. Total disinfection costs are rough Rp. 1,018,210.73. Water quality, lamp output power, and exposure distance affect lamp intensity. The lamp's electric power controls the beam's intensity; the more power, the more emission. The emitted power isn't equal to the lamp's electric power. According to the state electricity provider, families with a 900VA power limit will pay Rp. 1,352/kWh in July-September 2021. Nine 30-W bulbs irradiate bacteria. The lights will run for 24 hours non-stop. Hence the monthly electricity usage is 194.4 kWh or Rp 262.829.00.